Physical Activity with Sports Scientist (PASS) programme to promote physical activity among patients with non-communicable diseases: a pragmatic randomised controlled trial protocol - Wattanapisit, Apichai; Hemarachatanon, Poramet; Somrak, Kamlai; Manunyanon, Saranrat; Wattanapisit, Sanhapan; Amornsriwatanakul, Areekul; Katewongsa, Piyawat; Sangkaew, Sorawat; Vichitkunakorn, Polathep; Lee, Ping Yein; Ramdzan, Siti Nurkamilla; Salim, Hani; et al. (BMJ Publishing Group, 2024)
Physical activity (PA) effectively prevents and treats non-communicable diseases in clinical settings. PA promotion needs to be more consistent, especially in busy primary care. Sports scientists have the potential to support PA promotion in primary care. The Physical Activity with Sports Scientist (PASS) programme is created to personalise PA promotion led by a sports scientist in a primary care clinic. A pragmatic randomised controlled trial with two parallel groups will be conducted at a family medicine clinic. Physically inactive participants aged 35–70 years who have type 2 diabetes mellitus, hypertension or dyslipidaemia will be invited. The control group (n=60) will receive usual care. The intervention group (n=60) will receive the PASS programme and usual care. The PASS programme will consist of a tailored PA prescription after the physician’s consultation at the first visit and monthly phone follow-ups. The primary outcome is the proportion of participants who have achieved the PA goal defined as aerobic activity (≥150 min/week of moderate to vigorous-intensity PA), muscle-strengthening activity (≥2 days/week of moderate or greater intensity) and multicomponent PA (≥2 days/week of moderate or greater intensity). Secondary outcomes are body composition and physical fitness. The primary and secondary outcomes will be measured and compared between the control and intervention groups at visit 1 (month 0: baseline measurements), visit 2 (months 3–4: follow-up measurements), visit 3 (months 6–8: endpoint measurements) and visit 4 (months 9–12: continuing measurements). The study protocol was registered with the Thai Clinical Trials Registry. Trial registration number: TCTR20240314001.